# If \[x = a{\sin ^3}\theta \] and \[y = a{\cos ^3}\theta \], then find the value of \[\dfrac{{dy}}{{dx}}\].

Answer

Verified

362.1k+ views

Hint: First find the value of \[\dfrac{{dx}}{{d\theta }}\] and \[\dfrac{{dy}}{{d\theta }}\], then divide them to get \[\dfrac{{dy}}{{dx}}\]. Simplify the answer to express it in terms of x and y.

Let us start solving by finding the expression for \[\dfrac{{dx}}{{d\theta }}\].

\[\dfrac{{dx}}{{d\theta }} = \dfrac{d}{{d\theta }}(a{\sin ^3}\theta )\]

We can use \[\dfrac{d}{{dx}}(a{x^3}) = 3a{x^2}\] to simplify the equation.

\[\dfrac{{dx}}{{d\theta }} = 3a{\sin ^2}\theta \dfrac{d}{{d\theta }}(\sin \theta )\]

We know that \[\dfrac{d}{{dx}}(\sin x) = \cos x\], hence, we have the following:

\[\dfrac{{dx}}{{d\theta }} = 3a{\sin ^2}\theta \cos \theta .............(1)\]

Now, let us find the expression for \[\dfrac{{dy}}{{d\theta }}\].

\[\dfrac{{dy}}{{d\theta }} = \dfrac{d}{{d\theta }}(a{\cos ^3}\theta )\]

We can use \[\dfrac{d}{{dx}}(a{x^3}) = 3a{x^2}\] to simplify the equation.

\[\dfrac{{dx}}{{d\theta }} = 3a{\cos ^2}\theta \dfrac{d}{{d\theta }}(\cos \theta )\]

We know that \[\dfrac{d}{{dx}}(\cos x) = - \sin x\], hence, we have the following:

\[\dfrac{{dx}}{{d\theta }} = - 3a{\cos ^2}\theta \sin \theta ............(2)\]

We know that,

\[\dfrac{{dy}}{{dx}} = \dfrac{{\dfrac{{dy}}{{d\theta }}}}{{\dfrac{{dx}}{{d\theta }}}}...........(3)\]

Using equation (1) and equation (2) in equation (3), we have:

\[\dfrac{{dy}}{{dx}} = \dfrac{{3a{{\sin }^2}\theta \cos \theta }}{{ - 3a{{\cos }^2}\theta \sin \theta }}\]

Cancelling common terms in the numerator and the denominator we have:

\[\dfrac{{dy}}{{dx}} = - \dfrac{{\sin \theta }}{{\cos \theta }}\]

We know that \[\dfrac{{\sin \theta }}{{\cos \theta }} = \tan \theta \], hence we have:

\[\dfrac{{dy}}{{dx}} = - \tan \theta ..........(4)\]

We can write equation (4) in terms of x and y.

Let us find the value of \[\dfrac{x}{y}\].

\[\dfrac{x}{y} = \dfrac{{a{{\sin }^3}\theta }}{{a{{\cos }^3}\theta }}\]

Simplifying, we get:

\[\dfrac{x}{y} = \dfrac{{{{\sin }^3}\theta }}{{{{\cos }^3}\theta }}\]

\[\dfrac{x}{y} = {\tan ^3}\theta \]

Let us compute \[\tan \theta \] in terms of x and y by taking the cube root on both sides.

\[\tan \theta = \sqrt[3]{{\dfrac{x}{y}}}.........(5)\]

Substituting equation (5) in equation (4), we get:

\[\dfrac{{dy}}{{dx}} = - \sqrt[3]{{\dfrac{x}{y}}}\]

Hence, the answer is \[ - \sqrt[3]{{\dfrac{x}{y}}}\].

Note: If you express the final answer in terms of \[\theta \], it is a wrong answer. Express the final answer in terms of x and y only.

__Complete step-by-step answer:__Let us start solving by finding the expression for \[\dfrac{{dx}}{{d\theta }}\].

\[\dfrac{{dx}}{{d\theta }} = \dfrac{d}{{d\theta }}(a{\sin ^3}\theta )\]

We can use \[\dfrac{d}{{dx}}(a{x^3}) = 3a{x^2}\] to simplify the equation.

\[\dfrac{{dx}}{{d\theta }} = 3a{\sin ^2}\theta \dfrac{d}{{d\theta }}(\sin \theta )\]

We know that \[\dfrac{d}{{dx}}(\sin x) = \cos x\], hence, we have the following:

\[\dfrac{{dx}}{{d\theta }} = 3a{\sin ^2}\theta \cos \theta .............(1)\]

Now, let us find the expression for \[\dfrac{{dy}}{{d\theta }}\].

\[\dfrac{{dy}}{{d\theta }} = \dfrac{d}{{d\theta }}(a{\cos ^3}\theta )\]

We can use \[\dfrac{d}{{dx}}(a{x^3}) = 3a{x^2}\] to simplify the equation.

\[\dfrac{{dx}}{{d\theta }} = 3a{\cos ^2}\theta \dfrac{d}{{d\theta }}(\cos \theta )\]

We know that \[\dfrac{d}{{dx}}(\cos x) = - \sin x\], hence, we have the following:

\[\dfrac{{dx}}{{d\theta }} = - 3a{\cos ^2}\theta \sin \theta ............(2)\]

We know that,

\[\dfrac{{dy}}{{dx}} = \dfrac{{\dfrac{{dy}}{{d\theta }}}}{{\dfrac{{dx}}{{d\theta }}}}...........(3)\]

Using equation (1) and equation (2) in equation (3), we have:

\[\dfrac{{dy}}{{dx}} = \dfrac{{3a{{\sin }^2}\theta \cos \theta }}{{ - 3a{{\cos }^2}\theta \sin \theta }}\]

Cancelling common terms in the numerator and the denominator we have:

\[\dfrac{{dy}}{{dx}} = - \dfrac{{\sin \theta }}{{\cos \theta }}\]

We know that \[\dfrac{{\sin \theta }}{{\cos \theta }} = \tan \theta \], hence we have:

\[\dfrac{{dy}}{{dx}} = - \tan \theta ..........(4)\]

We can write equation (4) in terms of x and y.

Let us find the value of \[\dfrac{x}{y}\].

\[\dfrac{x}{y} = \dfrac{{a{{\sin }^3}\theta }}{{a{{\cos }^3}\theta }}\]

Simplifying, we get:

\[\dfrac{x}{y} = \dfrac{{{{\sin }^3}\theta }}{{{{\cos }^3}\theta }}\]

\[\dfrac{x}{y} = {\tan ^3}\theta \]

Let us compute \[\tan \theta \] in terms of x and y by taking the cube root on both sides.

\[\tan \theta = \sqrt[3]{{\dfrac{x}{y}}}.........(5)\]

Substituting equation (5) in equation (4), we get:

\[\dfrac{{dy}}{{dx}} = - \sqrt[3]{{\dfrac{x}{y}}}\]

Hence, the answer is \[ - \sqrt[3]{{\dfrac{x}{y}}}\].

Note: If you express the final answer in terms of \[\theta \], it is a wrong answer. Express the final answer in terms of x and y only.

Last updated date: 28th Sep 2023

â€¢

Total views: 362.1k

â€¢

Views today: 9.62k

Recently Updated Pages

What is the Full Form of DNA and RNA

What are the Difference Between Acute and Chronic Disease

Difference Between Communicable and Non-Communicable

What is Nutrition Explain Diff Type of Nutrition ?

What is the Function of Digestive Enzymes

What is the Full Form of 1.DPT 2.DDT 3.BCG

Trending doubts

How do you solve x2 11x + 28 0 using the quadratic class 10 maths CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Summary of the poem Where the Mind is Without Fear class 8 english CBSE

Difference Between Plant Cell and Animal Cell

What is the basic unit of classification class 11 biology CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

One cusec is equal to how many liters class 8 maths CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Give 10 examples for herbs , shrubs , climbers , creepers